Application for code editing with GPGPU pipelines - Syvenkyi, Petro; Yarkun, Volodymyr (Комп’ютерне моделювання та інформаційні технології, 2023)
This paper presents the advantages of using GPGPU pipelines for text processing and text drawing. Problems that arise when using GPGPU pipelines for text processing and text drawing are described. For text processing and text drawing, a code editor has been developed that can communicate with the GPU and use GPGPU pipelines. The main steps to achieve these goals are outlined.